Fortification of soft cheese made from ultrafiltered dromedary milk with Allium roseum powder: Effects on textural, radical scavenging, phenolic profile and sensory characteristics. (October 2020) - El Hatmi, Halima; Jrad, Zeineb; Mkadem, Wafa; Chahbani, Amna; Oussaief, Olfa; Zid, Malek Ben; Nouha, M'hiri; Zaidi, Slah; Khorchani, Sofiène; Belguith, Khaoula; Mihoubi, Nourhène Boudhrioua
Abstract: The purpose of this study was to evaluate the effect physical processes (ultrafiltration (UF) and skimming) processes and Allium roseum powder (AR) fortification on soft dromedary cheese properties. Six batches of cheese were manufactured and named Full-Fat-Cheese (FFC), Skim Cheese (SC) and Ultrafiltered-Cheese (UFC) unfortified and fortified with AR. Fat reduction and UF process affected significantly cheese yield (7 and 11.7%, respectively), physicochemical and textural parameters of cheese. Although AR incorporation improved the DPPH-inhibition of all the obtained categories of cheese (49.4 ± 2.6, 53.4 ± 2.0 and 82.4 ± 2.89 for FFC, SC and UFC, respectively). The color attributes differed between different samples (except a * parameter). LC-ESI-MS analysis revealed interesting phenolic compounds and enhancement of antioxidant scavenging activities in fortified and UF cheese. The FFC with and without AR samples received significantly the highest overall acceptability scores. Highlights: The ultrafiltration process (UF) is a promising technology for the production of dromedary cheese. UF improved dromedary cheese yield. Allium roseum improved the radical scavenging activity of dromedary cheeses. The full-fat dromedary cheese had the highest score for all sensory studied parameters compared to UF ones.